2003
DOI: 10.1046/j.1442-2026.2003.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of acute allergic diseases in an emergency department: An evaluation of one years’ experience

Abstract: Objective: There is limited available literature on the incidence of allergic diseases in ED. The objective of this study was to investigate the clinical records of patients admitted to the ED with a suspected allergic reaction. Methods: A 1 year retrospective study was carried out and data were collected from the patients’ computerized medical reports. Results: A total of 324 patients were admitted for an allergic event. Of those, 165 patients (50.9%) were female and their mean age was 55 ± 18.5 years. Diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 31 publications
1
42
0
1
Order By: Relevance
“…In 2003, Bellou and colleagues [17] reviewed the charts of 324 patients in France admitted to the emergency department for an allergic event and found that 31 (9.5%) patients were diagnosed with food allergy. Six (19%) of the food-allergy patients were observed to have anaphylactic shock.…”
Section: Assessment Of Emergency Department Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Bellou and colleagues [17] reviewed the charts of 324 patients in France admitted to the emergency department for an allergic event and found that 31 (9.5%) patients were diagnosed with food allergy. Six (19%) of the food-allergy patients were observed to have anaphylactic shock.…”
Section: Assessment Of Emergency Department Managementmentioning
confidence: 99%
“…A prompt and accurate diagnosis to identify those at greatest risk for adverse outcomes is essential for effective emergency management [16]. Given such large variability in anaphylaxis estimates in the general population -and in the emergency department -and reports suggesting that the prevalence of allergies is rising [1,17], more work is needed develop clinical definitions that would allow for better measurement of the actual prevalence of food-related allergic reaction and anaphylaxis, and promote improved management of these problems in the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies found that few patients were referred to an allergist after being seen for an acute reaction in community or hospital clinics (35,43,71) or the ED (26,31). However, one study found that allergy testing and follow-up were more frequent in children attending hospital clinics (28).…”
Section: Theme 3: Follow-up Carementioning
confidence: 99%
“…Although the emergency department (ED) plays a major role in the care of allergic disease,5 most studies to date have examined paediatric allergic reactions on an inpatient or outpatient basis or have focussed primarily on anaphylaxis 69. A recent study in Australia reviewed paediatric allergic reactions in the ED 10.…”
mentioning
confidence: 99%